The Welfare Consequences of Centralization: Evidence from a Quasi-Natural Experiment in Switzerland - Flèche, Sarah (The Review of Economics and Statistics, 2021)
Abstract Many countries are reallocating tasks and powers to more central levels of government. To identify centralization's welfare effects, I use a difference-in-differences design that relies on time and cross-cantonal variation in the implementation of centralization reforms in Switzerland. I find that centralization provokes significant decreases in residents' life satisfaction. I identify one mechanism driving the effect: the procedural disutility that individuals experience from having less influence over the formulation of political decisions. This effect is largest among individuals with higher expected benefits from being involved in the political decision process, with detrimental effects on local political participation.